Analisa Perbedaan Brand Image Situs Berita Berbahasa Indonesia Online Lokal - Wicaksono, Kuspuji Catur Bagus (Bina Nusantara University, 2011)
The amount of graduates and the availability of jobs are unbalanced, therefore unemployment is generalized; not only for uneducated but also those educated ones. This is supporting educational institutions to provide entrepreneurship subject for students to prepare themselves when they have no job and unemployment for the consequences.Â EntrpreneurialÂ education is not about theory but also field practice that involves every parts such as educational institutions, small-scale and major business, and also government. Education that moves accordingly with the development and field practice for students to be prepared for their graduation, whether or not being an entrepreneur.